Epidemiological Connections between Screens and Movement: Navigating Sedentary Behavior, Physical (In)Activity and Health Habits in Schoolchildren in Rio de Janeiro - Santos, Marco Antonio Ferreira dos (2024)
The study investigated physical activity habits, sedentary behaviors and exposure to screens in students from four school units in Rio de Janeiro, from a private educational institution, considering WHO guidelines. The research arises in response to the existing gap in understanding these patterns, given the lack of specific studies on schoolchildren in the region. Amid global concern about sedentary lifestyle, understanding specific patterns among students becomes crucial to developing effective strategies. The observational and exploratory study used the IPAQ questionnaire to collect data on physical activity and sports (AFES), as well as sedentary behaviors in 1668 students from four private school units. Statistical analysis, including Mann-Whitney and Kruskal-Wallis, sought to understand differences between sexes and school units. The results revealed an average of 4 days of walking of more than 10 minutes for males and 3 days for females. The average number of days performing moderate activities was 3, with males dedicating, on average, 100 minutes, and females 84 minutes. As for vigorous activities, both sexes had an average of 3 days, with males reporting 126 minutes and females 71 minutes. The total time of weekly physical activity was 260 minutes on average, with small variations between genders.With regard to inactivity and exposure to screens, the average time during the week was 574 minutes, while on weekends it was 510 minutes. Significant differences between sexes were evident in daily walking, moderate and vigorous activities, and sitting time during the week. Furthermore, there were variations between school units. The positive and significant correlation between the total number of days and the time of vigorous activities highlights the importance of differentiated strategies. These results provide valuable insights to guide health promotion policies, highlighting the need for personalized and contextualized approaches for this specific population.